MEDIA AGAMI UNTUK PEMBELAJARAN TEMATIK SISWA KELAS III SD - Remanda Wahyu Intisari; Marinda Sari Sofiyana; Mar’atus Sholihah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The problems obtained from the preliminary study indicated that there was no learning media for thematic learning for "Kenampakan Alam" material at grade III of elementary school. The direction of research to develop Agami media became learning support for grade III of elementary school, especially the theme of "Benda Disekitarku". This research and development applied the Borg and Gall models. This research was carried out in seven stages, namely potential and case, data accumulation, product design, design validation, design revision, exhibition product, and product revision. The type of data was feasibility and quality data of the media. The instrument was a validation questionnaire to calculate the feasibility of the media and students' response to criterion quality of media. The subjects in this study were 12 students at grade III of elementary school in Doko. The results of the validation by three experts, namely a media expert, a material expert, and a linguist expert, obtained an average of 95.2% with a feasible criterion. Then, the result of students' response got a score of 93.75% with a very feasible criterion and  was suitable for third grade elementary school students. The results from the validator’s assessment and student responses found that Agami media was feasible for thematic learning at grade III of elementary school. It is expected that the Agami media can be further developed by the next researchers until the 10 stage of Borg and Gall to achieve better educational goals and effectiveness in learning outcomes.